The four series of Malaysian Banknotes: a visual analysis of ringgit symbol / Mohammad Aaris Amirza and Mohamed Razeef Abdul Razak - Amirza, Mohammad Aaris; Abdul Razak, Mohamed Razeef (Faculty of Art & Design, 2022)
The currency symbol depicts a country's currency name since the 19th century. The currency symbol is found as part of the design elements of a banknote identity, which also reflects the country's ethos. The ringgit has a long history beginning. However, this progress revealed the inconsistency of the ringgit symbol in each banknote series. This paper aims to analyze the evolution of the ringgit symbol circulated in the series of Malaysian banknotes and the changes it has gone through since it was first issued on Malaysian banknotes right up to the fourth series. Using visual analysis of the ringgit symbol in all four banknotes series issued by Bank Negara Malaysia, this study found that the currency symbol used for the ringgit had different characteristics, mainly in banknotes issued in the second series, which disrupted the ringgit identity. The ringgit would become remarkable if attention were given to developing and introducing the RM symbol. An in-depth study to introduce an ideal form of the ringgit symbol design could help innovate Malaysia's monetary identity.